Analytical Investigation of the Existence and Ulam Stability of Integro-Differential Equations with Conformable Derivatives Under Non-Local Conditions - Fakhreddine, Seddiki; Hazaymeh, Ayman A; Aljazzazi, Mazin; Qaralleh, Reham; Bataihah, Anwar; Batiha, Iqbal M.; Hajaj, Rasha Ibrahim (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
This study examines an integro-differential equation involving fractional conformable derivatives and non-local conditions. It proves the existence and uniqueness of mild solutions by applying the Banach fixed-point theorem. Furthermore, it demonstrates a notable result about the existence of at least one solution, backed by conditions based on the Krasnoselskii fixed-point theorem. The investigation also explores the Ulam stability of integro-differential equations. To highlight the practical relevance and robustness of the findings, an illustrative example is provided.